Comparison of quality of life in patients with androgenetic alopecia and alopecia areata - Gonul,Muzeyyen (2018)
Abstract: Background: Androgenetic alopecia is one of the most common forms of hair loss. Alopecia areata is a common autoimmune disorder which causes hair loss. It has been previously reported that both alopecia disorders can have negative effects on quality of life. However, only a few studies have compared the effects of the two disorders. Objective: The aim is to show the impact of alopecia on patients' quality of life and compare patients with androgenetic alopecia and alopecia areata. Methods: 82 androgenetic alopecia and 56 alopecia areata patients were recruited. All patients were evaluated with the Hairdex scale and dermatology quality of life instrument in Turkish (TQL), and the scores were statistically compared according to age, sex, employment and education status, and severity of illness in the two groups. Also, female patients were statistically evaluated according to whether they wore headscarves. Results: Androgenetic alopecia patients had significantly higher total Hairdex scores in terms of emotions, functioning, and symptoms, while self-confidence was significantly higher in the alopecia areata patients. No significant differences were found in stigmatization or TQL scores between groups. The Hairdex scale and TQL scores did not show differences between the groups in terms of wearing headscarves. Study limitations: The validity and reliability of the Hairdex index have not been established in Turkey. Conclusions: Based on the Hairdex scale, our findings revealed that androgenetic alopecia patients are more affected by their disorder than alopecia areata patients. Although androgenetic alopecia is common and neither life-threatening nor painful, it is a stressful disorder with increased need for improvement in the patient's quality of life.